Nói ngọng : the social correlates of /l/ and /n/ in Vietnamese - Hoang, Nam Phuong (2019)
In this paper I investigate the phenomenon of bidirectional sound change in the Northern Vietnamese Dialect, particularly the expression of phonemic /n/ as [l] and the reverse expression of phonemic /l/ as [n]. The aim is to determine the nature of the sound changes, that is, whether they are phonologically motivated or sociophonetically motivated. The results reflect direct correlations between the speaker’s production of the sound changes /n/→[l] and/or /l/→[n] and her gender, educational attainment, as well as the geographical area she is from. Interaction effects are also found with certain pairs of social variables. These findings support the conclusion that the sound change is sociophonetically driven.